Engineering stable Amlodipine suspensions for flexible compounding at King Khaled University Hospital - Ehab Elzayat; Hadyah F. Alotaibi; Mohamed H. Al-Agamy; Lama A. Alharabi; Mohammed R. Alhuzani (Saudi Pharmaceutical Journal)
Abstract Extemporaneous liquid formulations are crucial for patients unable to swallow solid dosage forms. While the United States Pharmacopeia (USP) recommends a 3-month beyond-use date for extemporaneous Amlodipine suspensions, uncertainties persist regarding the impact of active pharmaceutical ingredient (API) source variability, the confirmation of extended in-use stability, and the practical challenges of adapting formulations to local market raw material availability. This study aimed to address these gaps by investigating the physicochemical and microbiological stability of extemporaneous Amlodipine suspensions prepared from different API sources and stored under simulated in-use and closed conditions for 3 months. Eight formulations were prepared using different dosage forms (tablets or capsules), manufacturers (brand or generic), strengths (5 mg or 10 mg), and storage conditions. Physical stability was assessed via organoleptic properties and pH measurements, chemical stability via a validated ultra-performance liquid chromatography-ultraviolet method, and microbiological stability through total aerobic microbial count and total yeast and mold count. All formulations demonstrated stability over 3 months at 5°C, with drug content maintained (mean 103.94% ± 1.79 SD, range 101.79–107%) of the initial concentration and no microbial growth detected, even under in-use conditions. No significant differences were observed between tablet- and capsule-based preparations. These findings confirm the United States Pharmacopeia’s 3-month beyond-use date recommendation and highlight the potential for more flexible preparation methods, including alternatives required by local market shortages. Our findings also support a 3-month in-use stability, which could improve patient convenience, reduce medication waste, and provide a more sustainable compounding approach at King Khaled University Hospital.